Nivel de caries y placa bacteriana en escolares. Sector 4. Riobamba, 2021 - Verónica Cecilia, Chacha Mancero (2020)
Abstract This research project aimed to analyze the level of caries, bacterial plaque, and the level of personal knowledge about oral health in students at four sectors in Riobamba. It was a descriptive research project with a cross-sectional qualitative approach. A survey was applied as a technique for data collection and a questionnaire as an instrument to assess student oral health. The project worked with the entire population, which was made up of 100 third-year high school students, and, likewise, 100 parents who, through informed consent, agreed to participate voluntarily. The results were analyzed in the statistical software SPSS v.25. Regarding the knowledge level, it was demonstrated that 64% of the population has a lousy knowledge level. The community CPOD index obtained a value of 11.84 (a very high range). Regarding the CPOD level, 55% was obtained (high range), and for the O'Leary index, 69% (questionable range) was obtained. Finally, a significant statistical association was found between the variables: "CPOD index percentage" and "Parents go to the dentist regularly," obtaining a low and negative correlation. Keywords: level of knowledge, oral health, CPOD index.